An Analysis of the Quality of Life of Children Experiencing Stunting and Wasting Born to Adolescent Mothers in the Alak District - Nenogasu, Yeri Delsia; Wulandari, Estiyani; Buan, Gerda N. (Journal of Maternal and Child Health, 2025)
Background: Adolescent pregnancy remains a prevalent global issue with well-documented causes. However, it contributes significantly to nutritional challenges among young children, including stunting and wasting. This study aims to assess the impact of neonatal health, maternal caregiving practices, incidence of illness, disease prevention efforts, and nutritional intake on the quality of life of stunted and wasted children aged 37–60 months born to adolescent mothers. Subjects and Method: This study is analytical correlational research using a cross-sectional approach. The study is conducted in Alak District (Consisting of Penkase, Alak, Naoini, and Manutapen Community Health Centers), Kupang City, from September to October 2024. The sample comprises 50 mother-child pairs selected based on specified inclusion criteria. Data collection, including primary and secondary sources, was conducted from September to October 2024 following ethical approval. The study aims to analyze the effects of latent variables within a factor model related to the quality of life of children. These latent variables include the newborn’s health history, maternal caregiving practices, illness occurrence, disease control efforts, nutritional intake, and the child’s quality of lifePartial Least Squares (PLS) analysis was performed using the Smart PLS 3.0 software. Results: The study findings reveal that newborn health, maternal caregiving practices, illness incidence, disease control efforts, and nutritional intake have both direct and indirect positive effects on children's quality of life. Significant direct positive relationships were observed between maternal caregiving practices and nutritional intake (T-statistic: 3.307), maternal caregiving practices and disease control efforts (T-statistic: 2.151), and disease control efforts and children’s quality of life (T-statistic: 2.578). Conclusion: Preventing adolescent pregnancy and childbirth is crucial, as it significantly impacts the long-term growth and development of children.